Managing Subnational Credit and Default Risks - Waibel, Michael; Liu, Lili (2012)
As a result of worldwide decentralization, subnational debt is rising. Subnational debt crises in major developing countries in the 1990s have led to strengthened regulatory frameworks for subnational borrowing and insolvency. With the fragility of the global recovery and increasing public debt, and the structural trends of decentralization and urbanization, it becomes more important to prudently manage subnational default risks. Although the regulatory frameworks share central features, the historical context and entry points for reform drive variations across countries. Addressing soft budget constraints is integral to the regulatory framework. Ex ante fiscal rules for subnational governments attempt to limit default risks; ex post regulation predictably allocates default risk, while providing breathing space for orderly debt restructuring and fiscal adjustment, as well as the continued delivery of essential public services. The regulatory reforms are inseparable from the reform of broader intergovernmental fiscal systems and financial markets.